2019
DOI: 10.1001/jamapediatrics.2019.2430
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Trends of Overweight and Obesity in European Children From 1999 to 2016

Abstract: IMPORTANCE Studies of trends in excess weight among European children throughout the last few decades have rendered mixed results. Additionally, some studies were outdated, were based on self-reported weight and height, or included only a few European countries.OBJECTIVE To assess prevalence trends in measured overweight and obesity among children across Europe from 1999 to 2016 using a systematic methodology.DATA SOURCES MEDLINE, Embase, CINAHL, and Web of Science were searched from their inception until May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
179
7
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(221 citation statements)
references
References 158 publications
14
179
7
21
Order By: Relevance
“…Aditionally we examined weight development per ethnic and SES groep, stratified by BMI category at age 5. We observed a conversion to normal weight in most groups, which is not in line with a study in [6][7][8][9][10][11][12] year old Norwegian children, where they found that overweight children tended to gain more weight than normal-weight children [24]. But the conversion to normal weight differed per ethnic and SES group.…”
Section: Sensitivity Analyses Dietary Patterns and Weight Developmentcontrasting
confidence: 88%
See 2 more Smart Citations
“…Aditionally we examined weight development per ethnic and SES groep, stratified by BMI category at age 5. We observed a conversion to normal weight in most groups, which is not in line with a study in [6][7][8][9][10][11][12] year old Norwegian children, where they found that overweight children tended to gain more weight than normal-weight children [24]. But the conversion to normal weight differed per ethnic and SES group.…”
Section: Sensitivity Analyses Dietary Patterns and Weight Developmentcontrasting
confidence: 88%
“…In recent years, research and Public Health has focussed on the high prevalence of obesity and overweight among children, mainly present in ethnic minority and lower Socio-economic (SES) groups [1,2,3,4]. Concurrently, there is evidence of a growing prevalence of underweight in children of native origin in high-income countries [5,6]. Although it is not clear how important this trend is for clinical practice, both underweight and overweight/obesity are a risk factor for health problems in later life [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overweight and obesity (OW-OB) epidemic spread rapidly in the 1990s and now affects increasingly younger children [1]. This matters because obese children are more likely to become obese adults and experience adverse health consequences [2].…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean region displays a particularly worrisome trend in childhood obesity. A recent study showed an increase in the prevalence of overweight and obesity from 22.9% in 1999 to 25.0% in 2016 among children aged 2 to 13 years in the Mediterranean part of Europe [15]. One of the explanations for this trend is departure from the traditional lifestyle and Mediterranean diet, especially in younger people from Mediterranean countries [16,17].…”
Section: Introductionmentioning
confidence: 99%